Modeling study on the influence of the strip filling mining sequence on mining‐induced failure - Ning Jiang (Energy Science & Engineering, 2020)
Abstract The strip filling mining method can solve the problems related to mining under structures, under aquifers, and under infrastructure (3U coal seams), while the reasonable selection of the mining and filling sequence still requires further investigation. The current study was conducted to investigate the stress and surface subsidence of a filling body (or coal pillar) under two filling sequences through theoretical analysis, similar simulation tests, and numerical simulations. To achieve optimal filling materials for the Liudong Coal Mine, a low‐strength similar paste filling material composed of fly ash, gypsum, and sand was developed. The relationships between the strength and the cement ratio and between the strength and the sand‐binder ratio were discussed. Similar simulation tests showed that mining scheme 1 (mining before filling) could lead to the formation of an isolated island coal pillar in the mining process, mining scheme 2 (filling before mining) had less influence on surface subsidence, and the stress on the filling body was smaller for scheme 2 than for scheme 1. The distributions of the stress and plastic zone in the two different mining and filling sequences were obtained through numerical simulations. The method of first filling and then mining could greatly reduce the stress concentration and plastic zone during the mining process. In summary, mining scheme 2 (filling before mining) can avoid the formation of isolated island coal pillars in the process of mining, and without considering other factors, scheme 2 should be adopted as much as possible.